2022
DOI: 10.1111/1751-2980.13134
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation may reduce the mortality of patients with severe and fulminant Clostridioides difficile infection compared to standard‐of‐care antibiotics in a community hospital

Abstract: Objectives Clostridioides difficile infection (CDI) is known for significant morbidity and mortality. Fecal microbiota transplantation (FMT) is an effective therapy for recurrent and resistant CDI. However, its impact on the mortality rate of patients with severe and fulminant CDI has not been rigorously studied yet. We aimed to evaluate the effectiveness of FMT on the mortality rate of patients with severe or fulminant CDI in a community hospital system. Methods Our study included 106 inpatients with severe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Another retrospective series examined mortality in patients with either fulminant CDI or severe refractory CDI before and after implementation of an inpatient FMT program; the authors found that CDI-related mortality was significantly decreased in both cohorts of patients after implantation of the inpatient FMT program [4]. A retrospective series reported mortality in patients with severe or fulminant CDI who received FMT and demonstrated reduced mortality when evaluated using univariable analysis but not when evaluated by multivariable analysis; these findings may have been due to the small sample size [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective series examined mortality in patients with either fulminant CDI or severe refractory CDI before and after implementation of an inpatient FMT program; the authors found that CDI-related mortality was significantly decreased in both cohorts of patients after implantation of the inpatient FMT program [4]. A retrospective series reported mortality in patients with severe or fulminant CDI who received FMT and demonstrated reduced mortality when evaluated using univariable analysis but not when evaluated by multivariable analysis; these findings may have been due to the small sample size [20].…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of expanding the indications of FMT to primary CDI have been proposed, and trials are currently underway. Additionally, it has been reported that FMT may reduce the mortality of patients with severe and fulminant CDI when compared to standard antibiotic therapy 11 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that FMT may reduce the mortality of patients with severe and fulminant CDI when compared to standard antibiotic therapy. 11 The latest microbiota-based therapeutics originating from FMT mainly involve the application of a washed preparation of fecal microbiota using automatic machine and device in China, 12,13 and the development of fecal microbiota suspension (RBX2660) and collection of Firmicutes spores from feces (SER-109) in the United States. 6,7 An improved method of FMT based on the automatic washing process and the related delivery decisions was developed as washed microbiota transplantation (WMT), 14 of which a consensus has been established by the FMT-standardization Study Group in China in 2020.…”
Section: Introductionmentioning
confidence: 99%